Comparison of Antitumour Activities of Heated and Raw Garlic Extracts on Fibrosarcoma in Mice - H Shirzad (Babol University of Medical Sciences, 2012)
BACKGROUND AND OBJECTIVE: Garlic has been shown to have anti-tumoral and anti-metastatic activities in some kinds of cancer. Therefore, it may be effective against fibrosarcoma. The effect of heating on garlic ingredients and its benefits are not clear. Therefore, in this study the effect of heating of garlic on the growth of WEHI-164fibrosarcoma cells in Balb/c mice was examined. The amounts of phenolic compounds and antioxidant capacity of heated and unheated garlic were also determined.METHODS: In an experimental study 40 inbred Balb/c mice were divided into 5 groups of 8 each. A single aliquot of 5 × 106 cells/100 µl WEHI-164 cells was injected subcutaneously in the chest of each animal. Groups 1, 3 and 5 received normal saline (0.2 ml), heated and unheated garlic (20 mg/kg) for two weeks before and three weeks after cell injection, and groups 2 and 4 received unheated and heated garlic, respectively. The mean size of tumors, antioxidant activity and phenolic compounds were measured and compared with each other.FINDINGS: The mean size of tumor in groups which received unheated garlic extract was smaller than that of heated group. Significant differences could be seen in the final last 6 days of experiment, so that the mean sizes of tumors on the 21st day of study was110±86 mm2in heated and 760±79 mm2in raw garlic groups (p0.05). The amount of total phenolic compounds in raw garlic (12.61 mg/gr) was more than heated garlic (1.07 mg/gr) (p>0.05).CONCLUSION: Garlic consumption may have important role in control and prevention of fibrosarcoma growth. But heating may decrease the phenolic compounds, antioxidant capacity and anticancer effect of garlic.